Household resource management practices of selected elderly members in San Jose Del Monte - Conde, Anna Christina B.; Bantang, Joanne Reandelar (2010.)
ABSTRACT This is a qualitative research that aims to study the household resource management practices of the elderly respondents in San Jose del Monte, Bulacan. Twenty respondents were purposively selected for the interview with the following criteria: they must be at least 60 years of age. are in healthy condition and are living with a nuclear family. The research shows that the elderly respondents contribute the following resource management practices in their household: care and maintenance of household materials, time and financial management and work simplification. The practices, including the values and principles behind these practices, are something that the family can really learn from and treasure. These practices are the same things that the elderly members want to impart to other household members through demonstration and dirct (verbal) instruction. One respondent shared a unique strategy that is through supervised simulation of the household tasks. Most of the respondents do not encounter much difficulty in transferring the household resource management practices owing to the effective strategies. Some, however, experienced that their recipient, i.e. their grandchildren, lack enthusiasm and skills to learn those practices. For the elderly members, they need creative ways and strategies in imparting their legacy to the latter generations. Thus, it is recommended that the HE trainers design community-based training programs that will help enrich the skills of the elderly by including recent strategies and techniques in teaching and in household resource management. It is also recommended that HE educators include in the curriculum a special topic on the Filipino elderly population as they are key participants in family management. There are also interesting topics that surfaced in the course of the research. One, the elderly people's value for health and religiosity merits a closer examination. Two, there can be an impact evaluation of effective strategies in teaching household resource management practices to the younger generation. Three, a comparative study can also be done exploring the situation of the elderly living alone and their contributions and sense of self-worth in contrast to those living with their children.
Thesis (B.S. Home Economics)--University of the Philippines Diliman.
Keywords: Life skills; Lifestyles